2016
DOI: 10.1016/j.yjmcc.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

GsMTx4-D is a cardioprotectant against myocardial infarction during ischemia and reperfusion

Abstract: GsMTx4 is a selective inhibitor of cationic mechanosensitive ion channels (MSCs) and has helped establish the role of MSCs in cardiac physiology. Inhomogeneous local mechanical stresses due to hypercontracture and swelling during ischemic reperfusion injury (IRI) likely induce elevated MSC activity that can contribute to cation imbalance. The aim of this study was to determine if the D enantiomer of GsMTx4 can act as a cardioprotectant in a mouse IRI model. Ischemia and reperfusion involved ligating a coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 70 publications
3
31
0
Order By: Relevance
“…The 34-amino acid peptide (Alomone labs, STG-100) is a member of the Inhibitory Cysteine Knot family with six cysteines, is a nontoxic component of tarantula venom, and functions as a negative allosteric modulator of mechanoreceptors (Suchyna et al, 2000). The D and L enantiomers of GsMTx4 have almost identical activity (Wang, Ma, Sachs, Li, & Suchyna, 2016) which suggests that its mechanism is not reliant on direct stereo-chemical interactions (Gnanasambandam et al, 2017). Instead, it has high affinity for lipid bilayers and its ability to partition into membranes and inhibit mechanosensitive ion channel opening appears key to its mechanism of action as a gating modifier of Piezo1 (Gottlieb, Suchyna, & Sachs, 2007).…”
Section: Reagentsmentioning
confidence: 99%
“…The 34-amino acid peptide (Alomone labs, STG-100) is a member of the Inhibitory Cysteine Knot family with six cysteines, is a nontoxic component of tarantula venom, and functions as a negative allosteric modulator of mechanoreceptors (Suchyna et al, 2000). The D and L enantiomers of GsMTx4 have almost identical activity (Wang, Ma, Sachs, Li, & Suchyna, 2016) which suggests that its mechanism is not reliant on direct stereo-chemical interactions (Gnanasambandam et al, 2017). Instead, it has high affinity for lipid bilayers and its ability to partition into membranes and inhibit mechanosensitive ion channel opening appears key to its mechanism of action as a gating modifier of Piezo1 (Gottlieb, Suchyna, & Sachs, 2007).…”
Section: Reagentsmentioning
confidence: 99%
“…The D-form of GsMTx4 has now been tested in vivo in mouse models of cardiac ischemic reperfusion injury [106] and muscular dystrophy [107], and shown to be an effective muscle protectant. In a mouse model of ischemic reperfusion injury GsMTx4-D was injected by intravenous administration during the ischemic event and pretreatment subcutaneously for a two day prior to ischemic challenge.…”
Section: Therapeutic Potential Of Gsmtx4mentioning
confidence: 99%
“…GsMTx4 has revealed that MSCS “apparently” contribute significantly to normal short-term and developmental physiology (examples: arterial pressure regulation [110, 111, 119, 120], skeletal muscle pressor reflex [121], cardiac stretch induced slow force response [122], RBC volume regulation [123, 124], neuronal touch and pain sensation [125127], mechanotransduction of sound by OHCs [128, 129], serotonin release by gut epithelium [130], renal epithelium luminal pressure detection [131], etc.). Interestingly, when injected over 6 weeks, the GsMTx4 exposure reached concentrations in most tissues that would inhibit MSCs (nervous system is an exception – GsMTx4 does not appear to cross the blood brain barrier [106, 107]), but with no detectable effect on normal physiology [107]. We also showed that IV injection into telemetered free-roaming ferrets had no acute effect on normal cardiac hemodynamic or electrical properties [106].…”
Section: Mscs In Normal Physiology Versus Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of KB-R7943 (10 µmol/L) was applied for cell study; however, for the whole animal study, a higher concentration (30 µmol/L) was used similar to what is cited in the literature. [54][55][56] The other chemicals were obtained from Fisher Scientific (Santa Clara, CA, USA).…”
Section: Chemicalsmentioning
confidence: 99%